SMART CONTRACTS TECHNOLOGY AND AVOIDANCE OF DISPUTES IN CONSTRUCTION CONTRACTS - Cristian Răzvan RUGINĂ (Challenges of the Knowledge Society)
Claims and disputes had become endemic in the construction industry and, in spite of the continuous developments of the standard forms of contracts and consensual dispute resolution schemes from the past years, there is no indication that the incidence of claims and disputes is decreasing. Traditionally it is considered that the most often contractual disputes result from inappropriate or unclear risk allocation in the contract, or from breach of contract. However, recent studies suggest that these are only the apparent causes of disputes, the most profound one being the improper behavior of the parties involved in the contract determined by their asymmetric information and conflicting interests regarding the contract. This paper analyzes the most popular disputes avoidance methods and techniques currently used in construction industry, the most common causes of construction disputes, the behavioral risk as the main source of construction disputes, and how the available information and digital technologies would be embraced in the near future to prevent the disputes in construction contracts in an efficient manner.